Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/1129729821998836
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of catheter-related bloodstream infections in patients undergoing hemodialysis: A single center experience

Abstract: Background: Here we aimed to investigate the predictors of catheter-related bloodstream infections (CRBSI) in patients with acute kidney injury or chronic kidney disease who required renal replacement therapy through a non-tunneled hemodialysis catheter. Methods: A total of 111 patients who received non-tunneled hemodialysis catheters were retrospectively evaluated. Patients were divided into two groups; those who developed CRBSI and those who did not. Patient’s demographic data, laboratory results at admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 31 publications
1
9
1
1
Order By: Relevance
“…Individuals with diabetes, a longer catheter and a left internal jugular catheter placement had a considerably increased chance of developing CRBSI. 23,24 However, no meaningful correlation between any component and CRI was found in the current study.…”
Section: Discussioncontrasting
confidence: 81%
“…Individuals with diabetes, a longer catheter and a left internal jugular catheter placement had a considerably increased chance of developing CRBSI. 23,24 However, no meaningful correlation between any component and CRI was found in the current study.…”
Section: Discussioncontrasting
confidence: 81%
“…6,7,11,28,34 Conversely, we also found that a right sided CVC placement and elevated serum albumin levels decreased the risk of developing CRBSI, both of which were also consistent with published studies. 10,31 We attempted to identify infusion related risk factors that may in uence formation of CRBSI. Studies allude to the increased risk of CRBSI with infusion of blood products, intravenous medications and parenteral nutrition via catheter access.…”
Section: Discussionmentioning
confidence: 99%
“…1,5-9 CRBSI incidence varies from 0.6 to 6.5 episodes per 1000 catheter-days, depending on de nition, local policies for catheter placement and care, and duration of catheterization. 1,5,10,11 Staphylococcus spp. is the most common causative organism, however; infections may also be due to other gram positive or gram negative pathogens.…”
mentioning
confidence: 99%
See 2 more Smart Citations